2015
DOI: 10.1089/chi.2014.0098
|View full text |Cite
|
Sign up to set email alerts
|

A Positive Deviance Approach to Early Childhood Obesity: Cross-Sectional Characterization of Positive Outliers

Abstract: Objective: Positive deviance methodology has been applied in the developing world to address childhood malnutrition and has potential for application to childhood obesity in the United States. We hypothesized that among children at high-risk for obesity, evaluating normal weight children will enable identification of positive outlier behaviors and practices.Methods: In a community at high-risk for obesity, a cross-sectional mixed-methods analysis was done of normal weight, overweight, and obese children, class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 49 publications
3
19
1
Order By: Relevance
“…Similar to other research with Latino mothers, 22,40 participants in this study seemed to value family dinners, and most mothers reported eating dinner with their children. However, most participants reported that their child ate breakfast with siblings but without a parent.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Similar to other research with Latino mothers, 22,40 participants in this study seemed to value family dinners, and most mothers reported eating dinner with their children. However, most participants reported that their child ate breakfast with siblings but without a parent.…”
Section: Discussionsupporting
confidence: 83%
“…Other studies have found children’s food preferences to be a primary determinant of mothers’ child feeding decisions. 17 For instance, in a qualitative study of Latino parents of preschoolers, Foster et al 40 observed that parents of healthy weight children appeared to offer only healthy foods when they provided options to their children and to have a greater sense of control over food decisions, whereas parents of obese children seemed to feel less control over their children’s food choices and a greater tendency to respond to their children’s food preferences. Consistent with other research, 41 participants’ qualitative comments suggest that children’s prior intake may have also influenced the foods that mothers provided.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Persons facing social or economic obstacles to good health may nevertheless practise health-promoting behaviours when those behaviours are viewed as acceptable, affordable, effective and consistent with local culture. [5][6][7] In this study, we extend the idea of positive deviance from characteristics of individuals to those of communities 8 and hypothesise that communities may also possess collective attributes that allow them to outperform expectations given traditional risk indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Another study, conducted in a largely Hispanic community in Texas at high risk for childhood obesity, found unique feeding behaviours and healthy habits among parents with normal weight children. 1 However, it may be the case that features of communities can influence collective personal decisions about health behaviours, leading to positive deviant outcomes at the level of the group. Research on community-level positive deviance is sparse.…”
Section: Introductionmentioning
confidence: 99%
“…We recently completed a pilot study to examine the potential for identifying positively deviant behaviors and practices regarding childhood weight status in south Texas [7]. We subsequently designed the randomized clinical trial (RCT) reported herein to test whether these identified behaviors and practices could be implemented in an intervention using peer mentors.…”
Section: Introductionmentioning
confidence: 99%